Resected Pancreatic Cancer With N2 Node Involvement Is Refractory to Gemcitabine-Based Adjuvant Chemotherapy - Chen Liu MD, PhD; He Cheng MD; Kaizhou Jin MD, PhD; Zhiyao Fan MD; Yitao Gong MD; Yunzhen Qian MD; Shengming Deng MD; Qiuyi Huang MD; Quanxing Ni MD; Xianjun Yu MD, PhD; Guopei Luo MD, PhD (Cancer Control, 2020)
Lymphatic metastasis is a major determinant of the outcome of resected pancreatic cancer. Gemcitabine-based adjuvant chemotherapy can improve the outcome of resected pancreatic cancer. However, the efficacy of gemcitabine against pancreatic cancer stratified by nodal involvement is unclear. In this study, patients who had undergone curative resection of pancreatic adenocarcinoma (612 cases) were included. The efficacy of adjuvant gemcitabine-based regimen, stratified by nodal status (negative, positive) or N substage (N0, no nodal involvement; N1, 1-3-node involvement; N2, ≥4-node involvement), was examined. Both the node-negative (hazard ratio [HR] = 0.62, 95% confidence interval [CI], 0.44-0.87, P = .006) and node-positive subgroups (HR = 0.45, 95% CI, 0.33-0.62, P < .001) benefited from gemcitabine-based adjuvant chemotherapy. Patients with N0 (ie, the node-negative subgroup) or N1 (HR = 0.36, 95% CI, 0.25-0.52, P < .001) disease benefited from gemcitabine-based chemotherapy. However, patients with N2 tumors (HR = 0.95, 95% CI, 0.50-1.78, P = .867) had poor response to gemcitabine-based treatment. Therefore, we postulate that resected pancreatic cancer with N2 node involvement is refractory to gemcitabine-based adjuvant chemotherapy. A more intensive adjuvant regimen may be required for N2 subgroup patients.